PHYSICAL ACTIVITY AS A NON-PHARMACOLOGICAL INTERVENTION FOR INSOMNIA - Oliwia Barańska; Justyna Drożdżał; Małgorzata Chańko; Magdalena Rędaszka; Tymon Wojczulis; Anna Wojtkiewicz; Marta Kowalska (International Journal of Innovative Technologies in Social Science, 2026)
Insomnia, a prevalent sleep disorder affecting up to 18% of the population, is associated with significant health risks including depression, anxiety, cardiometabolic disease, and impaired physical and cognitive performance. Clinical guidelines prioritize non-pharmacological strategies such as cognitive-behavioral therapy for insomnia, with pharmacotherapy reserved for refractory cases. Physical activity has emerged as a promising adjunctive behavioral intervention, offering both sleep-specific and broad health benefits. This review synthesizes current evidence on exercise as a non-pharmacological intervention for insomnia, examining randomized controlled trials, epidemiological findings, and mechanistic studies. Across diverse populations, regular moderate-intensity physical activity - particularly aerobic exercise - improves sleep onset latency, efficiency, duration, and subjective quality. Additional benefits are observed with resistance, stretching, and mind-body modalities such as yoga and tai chi. Mechanisms include thermoregulatory cooling, circadian rhythm entrainment, neuroendocrine modulation, anxiety reduction, and enhanced sleep drive. Optimal outcomes are achieved with 150 minutes/week of moderate-intensity exercise, preferably in the morning or early afternoon; vigorous late-evening activity may be counterproductive. Integration with therapy and other treatments can amplify therapeutic effects, while tailoring type, intensity, and timing to patient characteristics enhances adherence and minimizes adverse effects. Given its accessibility, safety profile, and holistic benefits, physical activity should be considered a core component of insomnia management, offering a sustainable alternative or complement to pharmacological approaches.